Mucocutaneous hyperpigmentation as presentation of vitamin B12 deficiency: A case report and brief review - Prachi V Agrawal; Yugal K Sharma; Kirti S Deo; Rahul H Ranpariya; Pallavi Singh (Wolters Kluwer Medknow Publications, 2019)
Vitamin B12 deficiency presents usually with hematologic, gastrointestinal, neurologic, and less commonly, psychiatric, cardiovascular, and dermatological manifestations. A 20-year-old female presented with palmoplantar hyperpigmentation, accentuated over creases and knuckles. She also had intertriginous, perioral/intraoral hyperpigmentation, and gray, thin, lustreless hair. She consumed nonvegetarian diet occasionally. Histopathology revealed increased pigmentation of stratum malpighii. Hemoglobin, vitamin B12, and folate levels were reduced; RBC indices, deranged and parietal cell antibodies, weakly reactive. Pernicious anemia was diagnosed; the patient responded to intramuscular cobalamin injections. Review of Indian and global cases/case series of this deficiency with mucocutaneous presentation iterates knuckle hyperpigmentation to be its prime clinical marker. However, the nonvegetarians comprising a majority of participants in case series from India of vitamin B12 deficiency presenting with hyperpigmentation is confounding and necessitates reassessment with larger future studies. Moreover, increased awareness of the mucocutaneous signs-often nonspecific, subtle, or asymptomatic-of this widely pervasive deficiency among Indians may facilitate prompt management and rectify underreporting.